Student Interest in Class XI SMA Muhammadiyah 2 Yogyakarta in Online Learning in Biology Subjects Using Powerpoint as a Learning Media - Novita Amalia Anggraini; Shintia Oktaviana; Annisa Hanif Panjaitan; Ira Kusmawati; Much. Fuad Saifuddin; Gunarno Gunarno (Universitas Ahmad Dahlan, 2022)
This study aims to determine the learning interest of class XI students in biology subjects using powerpoint as a learning medium during the pandemic. The subjects of this study were students of class XI MIPA at SMA Muhammadiyah 2 Yogyakarta. To find out students' interest in learning using learning media in the form of PowerPoint, a survey method was used by distributing questionnaires via Google Form to students, where the researchers did not give treatment like an experiment. The results showed that the response agreed to the use of powerpoint as a medium for learning biology during a pandemic, it can be seen from the results of research on the aspect of feeling happy showing the response agreeing with the largest percentage, namely 99%, in the aspect of interest showing the response strongly agreeing with the largest percentage 86%, at The acceptance aspect shows a strongly agree response with the largest percentage, namely 98%, and the student involvement aspect shows a agree response with the largest percentage, namely 96%. Through this research, it is known that using powerpoint learning media in biology subjects can increase students' interest in learning.